Fibre-optic measurement of strain and shape on a helicopter rotor blade during a ground run: 2. Measurement of shape - Kissinger, Thomas; James, Stephen W.; Weber, Simone; Mullaney, Kevin; Chehura, Edmond; Pekmezci, Huseyin H.; Barrington, James; Staines, Stephen E.; Charrett, Thomas O. H.; Lawson, Nicholas J.; Lone, Mudassir; Atack, Richard; et al. (IOP Publishing, 2022)
Optical fibre strain and shape measurement sensors were deployed on a rotor blade during a full-speed helicopter ground run, with real-time data wirelessly streamed from rotor hub-mounted sensor interrogators. In part 2 of a 2-part paper series, two-dimensional direct fibre-optic shape sensing (DFOSS), using fibre segment interferometry-based interrogation is investigated. The concept of blade shape change visualisation over one rotation period using rotation displacement surfaces is introduced and the usefulness of DFOSS data to gain additional insights by determining operational modal frequencies independently for both horizontal and vertical vibration directions of the blade is demonstrated.